2019
DOI: 10.7819/rbgn.v21i2.3972
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Customer Inertia - An Investigation of Mobile Phone Services

Abstract: Purpose -In ongoing service sectors, some companies have high customer retention in spite of frequent consumer dissatisfaction and high complaint rates. This retention results from customer inertia. This paper aims to identify what influences this inertial behavior.Design/methodology/approach -Two competing conceptual models were conceived: a Base Model, which considers mediating effects, and a Rival Model, which considers only the direct effects on customer inertia. A survey was undertaken in Brazil. Mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Several studies found inertia was a crucial indicator of individuals' resistance behaviour (Polites and Karahanna, 2012; Auger et al. , 2016; Amoroso and Lim, 2017; de Mesquita and Urdan, 2019). In the mHRM context, employees are comfortable using the existing HRMS and do not want to take the risk of using a new platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies found inertia was a crucial indicator of individuals' resistance behaviour (Polites and Karahanna, 2012; Auger et al. , 2016; Amoroso and Lim, 2017; de Mesquita and Urdan, 2019). In the mHRM context, employees are comfortable using the existing HRMS and do not want to take the risk of using a new platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Factors that explain a high SI yet no actual exit may include the unattractiveness of alternatives and customer inertia (de Mesquita and Urdan, 2019; Gray et al , 2017) as well as customer’s opportunistic behavior (Wirtz and McColl-Kennedy, 2010) by which customers take advantage of their high level of SI as a threat to seek compensation. On the other hand, seasonality may be a factor that explains the phenomenon of low SI with actual customer exit since the fitness industry is highly affected by it, such that the number of memberships significantly increases in certain seasons, such as New Year and summertime but decreases in other seasons (ACAD, 2018; Minton, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…This is a natural and rational behavior. Mesquita & Urdan (2019) tested the cellular telephone sector and found a positive relationship between perceived quality and consumer inertia. Based on this, we propose the following hypotheses:…”
Section: Research Hypothesismentioning
confidence: 99%